Art therapy for military service members with post-traumatic stress and traumatic brain injury: Three case reports highlighting trajectories of treatment and recovery. (April 2019) - Jones, Jacqueline P.; Drass, Jessica M.; Kaimal, Girija
Highlights: The inclusion of art therapy into interdisciplinary treatment plans significantly improved patients' progress in addressing TBI and PTS. A stage-based outpatient art therapy program enabled patients to express, identify, articulate, and process chronic trauma-related symptoms. Engagement in outpatient art therapy program led to improved communication with providers and loved ones and improved quality of life. Service members continued utilizing coping skills and implement strategies developed through participation in art therapy in everyday life. Abstract: Advances in both military and medical technology have led to decreased mortality rates among military service personnel in the United States, yet have led to an increase in occurrences of traumatic brain injuries and post-traumatic stress disorder in military service personnel, often resulting in prolonged unresolved symptoms. The purpose of this article is to illustrate the implementation and effects of an art therapy program on military service personnel attending an outpatient military treatment facility. To this end, we present case reports of three military service personnel diagnosed with comorbid traumatic brain injury and post-traumatic stress and describe their participation in the art therapy program at Intrepid Spirit One, the National Intrepid Center of Excellence satellite site at Fort Belvoir Community Hospital. Through discussion of the therapist's subjective observations, as well as the patients' visual art productions and their personal verbal and written reflections on their experiences in art therapy and, eventually, on community art programs, this article highlights how art therapy was used to treat military trauma as part of a comprehensive integrative treatment program. The cases highlight how participation in a long-term, stage-based, structured art therapy program (through both group and individual sessions), enabled military service personnel to identify and articulate the complexity of their lingering trauma symptoms, fostering improvement in their communication with other treatment providers and loved ones, which, in turn, led to improvements in their overall quality of life.